Sibisa Toba Samosir (Bioclimatic Architecture) - Hajar Suwantoro; Teuku Ichwan Rudhie (Talenta Publisher, 2018)
Lake Toba is one of the ten most priority developing tourism destinations in Indonesia, as for 2019 President Joko Widodo targets one million Lake Toba visitors. Toba region strategic location, which surrounds Lake Toba, in addition to the variety of existing natural tourism and culture, become an attraction to the visitor. But, the facilities in this area tend to be an imbalance of what was targeted by the government. The planning of Sibisa Toba Samosir Business Hotel is expected to fulfill lodge accommodation to domestic or international tourists who come over to Lake Toba business activity. Tropical climate potential with the combination of daylight, wind, and rainfall can be a consideration in design. Design approach which initiates bioclimatic architecture can be an eco-friendly building. The sustainable design also can reduce energy usage in all buildings needs aspects.